Pemanfaatan Biogas dalam Pengurangan Risiko Paparan Limbah Peternakan - Agita, Agita; Prasasti, Corie Indria (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Cattle farms in densely populated areas have the potential to cause environmental pollution and health risks if the waste produced is not managed optimally. One possible solution is to implement appropriate waste management technology, such as biogas digesters, which can convert livestock manure into alternative energy for household needs. This community service activity was carried out in Wonocolo District, Surabaya City, from August to December 2024. The aim was to increase the capacity of livestock farmers in managing livestock waste using biogas digester technology through a series of educational activities, training, and mentoring on biogas digester construction. The results of the activity demonstrated the success of building a biogas digester unit that can be used by livestock farmers, and encouraged initiatives to replicate similar technology by other livestock farmers in the surrounding area. Challenges faced, such as temperature changes during the rainy season and social challenges, are important ingredients for increasing future innovation. Overall, this activity demonstrates that with the right support and active cross-sector participation, biogas technology can be adopted as a sustainable and environmentally friendly solution for livestock waste management.